Calculation of resources and an efficiency analysis of strategies in a game model of confrontation - Musayeva, M.A. (Numerical Methods and Programming (Vychislitel'nye Metody i Programmirovanie), 2020)
A game model of confrontation is formulated in the form of an attack and defense model, methods for calculating the resources of the confrontation parties are discussed, their efficiency is analyzed, and the existence conditions are given for an optimal solution to the considering problems.